1992
DOI: 10.2307/3283540
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomic Revision of the Genus Trichinella

Abstract: The analysis of genetic, biochemical, and biological data on about 300 Trichinella isolates, reported in the literature, allows a taxonomic revision of this genus. We propose the recognition of 5 sibling species, Trichinella spiralis (Owen, 1835) sensu stricto; Trichinella nativa Britov and Boev, 1972; Trichinella pseudospiralis Garkavi, 1972; Trichinella nelsoni Britov and Boev, 1972 sensu stricto; and Trichinella britovi n. sp., on the basis of biochemical and biological characteristics. Trichinella britovi … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
110
0
4

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 189 publications
(116 citation statements)
references
References 20 publications
2
110
0
4
Order By: Relevance
“…and specific antibody titres remained above cut-off level for the duration of the study (Fig. 2) (Ooi et al, 1986;Pozio et al, 1992a;Pozio et al, 1992b;Yao et al, 1997). The high reproductive capacity of T. spiralis in rats, as found here, support the general perception that pigs and rats are the most important hosts in the domestic cycle of infection (Schad et al, 1987;Leiby et al, 1988;Pozio et al, 1996).…”
mentioning
confidence: 96%
See 2 more Smart Citations
“…and specific antibody titres remained above cut-off level for the duration of the study (Fig. 2) (Ooi et al, 1986;Pozio et al, 1992a;Pozio et al, 1992b;Yao et al, 1997). The high reproductive capacity of T. spiralis in rats, as found here, support the general perception that pigs and rats are the most important hosts in the domestic cycle of infection (Schad et al, 1987;Leiby et al, 1988;Pozio et al, 1996).…”
mentioning
confidence: 96%
“…However, findings of natural infections in rats, suggest that moderate infectivity and persistence of T. britovi makes this genotype quite successful in infecting rats, though it cannot be maintained in the domestic cycle . A different situation is observed in Africa where T. nelsoni is the etiological agent of sylvatic trichinellosis Pozio et al, 1992a;Pozio et al, 1997 …”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Although there are no significant differences in morphology by scanning electron microscopy (Lichtenfels et al, 1983), the two gene types have different host specificity (Smith, 1985;Song et al, 1998;Kapel, 2000;Oivanen et al, 2002). Moreover, T. spiralis and T. nativa have different biological and biochemical characteristics (Pozio et al, 1992b;Song et al, 1994). A recent study showed that T. spiralis and T. nativa induced distinguishable histopathologic and humoral responses in raccoon dogs, there are also significant differences in the shapes and structures of the encapsulated cysts of these two parasites .…”
Section: ……………mentioning
confidence: 99%
“…The different numbers of the polypeptide fractions, the different electrophoretic mobility, different pI, as well as the studies of Pozio et al [ 14 ] give as grounds to assume that the water-soluble proteins of the isolates: ISS03, ISS13, ISS10, ISS02, ISS029, ISS035, belong to the species: T. spiralis, T. pseudospiralis, T. nativa, T. britovi, T. nelsoni and T. murrelli and display both common protein components as well as ones typical of the individual isolates and can be successfully implemented in the identification of various strains and isolates from the Trichinella genus.…”
mentioning
confidence: 99%